Dissolution and deacetylation of chitin in ionic liquid tetrabutylammonium hydroxide and its cascade reaction in enzyme treatment for chitin recycling. (15th February 2020) - Ma, Qinyuan; Gao, Xiuzhen; Bi, Xinyu; Han, Qi; Tu, Linna; Yang, Yupeng; Shen, Yanbing; Wang, Min
Graphical abstract: Highlights: Mild ionic liquids [TBA][OH] was employed on chitin for the first time. [TBA][OH] showed dissolution and deacetylation abilities on chitin. Deacetylation of chitin was positively correlated with the solubility of chitin. A combinational process of [TBA][OH] pretreatment and ReCDA were performed. The ReCDA activity on chitin was activated with [TBA][OH] pretreatment. Abstract: Chitin is the second most abundant renewable polymer on earth, and its deacetylated derivative, chitosan, is a highly useful biopolymer. This work studied for the first time the application of ionic liquid (IL) tetrabutylammonium hydroxide ([TBA][OH]) and chitin deacetylase from Rhodococcus equi CGMCC14861 (ReCDA) for the efficient conversion of chitin into chitosan at room temperature. Results confirmed that chitin had good solubility in 18 wt% aqueous [TBA][OH] solution at 80 ℃. In addition, efficient chitin deactylation was observed with high concentrations of [TBA][OH] exceeding 12 wt% and showing potential application in chitin conversion. ReCDA activity on chitin was activated by [TBA][OH] pretreatment. Sequential and simultaneous strategies were also compared, and the results showed that the simultaneous one-pot deacetylation provided the highest acetic acid yield of 3.78 mg/g chitin powder after 24 h. This study serves as a guide for the dissolution and deacetylation of chitin to produce high value-added chitosan products.